Virus-Induced Tubules: A Vehicle for Spread of Virions into Ovary Oocyte Cells of an Insect Vector - Liao, Zhenfeng; Mao, Qianzhuo; Li, Jiajia; Lu, Chengcong; Wu, Wei; Chen, Hongyan; Chen, Qian; Jia, Dongsheng; Wei, Taiyun (Frontiers in Microbiology, 2017)
Many arthropod-borne viruses are persistently propagated and transovarially transmitted by female insect vectors through eggs, but the mechanism remains poorly understood. Insect oocytes are surrounded by a layer of follicular cells, which are connected to the oocyte through actin-based microvilli. Here, we demonstrate that a plant reovirus, rice gall dwarf virus (RGDV), exploits virus-containing tubules composed of viral nonstructural protein Pns11 to pass through actin-based junctions between follicular cells or through actin-based microvilli from follicular cells into oocyte of its leafhopper vector Recilia dorsalis, thus overcoming transovarial transmission barriers. We further determine that the association of Pns11 tubules with actin-based cellular junctions or microvilli of the ovary is mediated by a specific interaction between Pns11 and actin. Interestingly, RGDV can replicate and assemble progeny virions in the oocyte cytoplasm. The destruction of the tubule assembly by RNA interference with synthesized double-stranded RNA targeting the Pns11 gene strongly inhibits transovarial transmission of RGDV by its vectors. For the first time, we show that a virus can exploit virus-induced tubule as a vehicle to overcome the transovarial transmission barrier by insect vectors.